From the History of International Cooperation of Uzbekistan - Shaxlo Kurbanova (Researchparks Publishing, 2021)
The author in this scientific article examines and analyzes the history of international cooperation of the Uzbek SSR during the reign of Sharaf Rashidov, as well as issues such as the export of machinery and equipment, the cost of products sent by Uzbekistan to the foreign market. In 1956, on the initiative of Indian writers, a meeting of Asian writers was held in Delhi. Among its participants were representatives of the USSR, China, Japan, Ceylon, North Korea, Burma and other countries. This meeting gave birth to the idea of creating a writers’ movement in Asia and Africa.